Optimization of Safety Factor by Genetic Algorithm of Circular Notched Carbon / Epoxy Laminate at Low Velocity Impact - Maamar, Djilali Beida; Zenasni, Ramdane (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2018)
This work deals with the application of the genetic algorithm to the determination of optimal safety factor of layered structure subjected to low velocity impact damage. These genetic algorithms are optimization algorithms based on the techniques derived from genetics and the natural evolution; crossovers, mutations, selection. The numerical modeling was carried out by the finite element software LS dyna which is coupled to the optimization program Ls-optui. The aim of this work is to minimize the safety factor based on the Tsai-Wu criterion for laminate.The optimization is held by evaluating the maximal energy that can undergo the material for a minimum safety factor. In this case a composite laminate of stacking [0/30/45/60/90/45]s with a circular notch drilled at defined location, then a laminate was targeted at the center by four impactors (cylinder, hemispherical, ball and truncated cone). The optimization was held in two phases; first without taking account the function of delamination and in the second phase with the function of delamination.